Quantifying Deforestation in Permanent Forest Reserve (PFR) in Northern Kelantan Using Remote Sensing and Geographic Information System - Setaiwan, Iwan (2001)
A study was carried out to monitor and quantify deforestation using remote sensing and GIS in the Permanent Forest Reserve (PFR), in northern part of Kelantan, Malaysia (latitudes 04°30'N to 06°15'N and longitudes of 101°20'E to 102°40'E). The PFR boundary map published by Kelantan State Forestry Department in 1989 was digitized using ARCIINFO 3.4.2 GIS software and used as basic data in the study. A Landsat TM image of 1997 of northern part of Kelantan (127/56 path and row) was enhanced, classified and vectorized using PCI 6.2 and ER Mapper 6.0 software to monitor and quantify deforestation. The extent of the forested area extracted from the Landsat TM images of 1 997 was about 329,349.23 ha. Results indicated that about 73,236.16 ha of the PFR area had been converted into non-forestry purpose within eight years (1989- 1997). The rate of deforestation was 2.27% per year. The PFR's area extent declined from 402,585 .39 ha in 1989 to 329,349.23 ha in 1997. The change from forest into mixed crop or rubber within eight years (1989-1997) was estimated to be 19,252.07 ha. However, about 53,984.09 ha of forest were changed into shrubs, while approximately 1,178.49 ha of forest were changed into grassland/open areas.